2023
DOI: 10.1038/s41598-022-27284-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to polystyrene microplastic beads causes sex-specific toxic effects in the model insect Drosophila melanogaster

Abstract: The toxicity of MPs on aquatic creatures has been extensively studied, but little attention was paid to terrestrial organisms. To fill this gab, we conducted a series of experiments using Drosophila as a model organism to understand whether exposure to different concentrations (0.005, 0.05, 0.5 µg/ml) of polystyrene microplastics (PS-MPs) beads (2 µm in size) can impact flies feeding activity, digestion and excretion. The ability of flies to distinguish between normal and PS-MPs treated food media was tested f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 77 publications
1
3
1
Order By: Relevance
“…This study revealed that the mortality rates were influenced by sex following acute inhalation exposure to CMIT/MIT. These findings are consistent with previous studies that have demonstrated sex-specific responses in parameters of toxicity, such as survival rate, in the D. melanogaster model (El Kholy and Al Naggar, 2023). Moreover, transcriptional alterations and metabolic responses were also shown to be sex-specific impacts on this model (Brown et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…This study revealed that the mortality rates were influenced by sex following acute inhalation exposure to CMIT/MIT. These findings are consistent with previous studies that have demonstrated sex-specific responses in parameters of toxicity, such as survival rate, in the D. melanogaster model (El Kholy and Al Naggar, 2023). Moreover, transcriptional alterations and metabolic responses were also shown to be sex-specific impacts on this model (Brown et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…Although previous research has shown that the toxicity of microplastics may vary with concentration [ 47 , 48 ], significant differences in bee body weight and sugar syrup consumption were only observed at 10 g/mL, not at 100 g/mL of both sizes of PS-MS, in the current study. Even though the cause is unknown, e.g., through disruption of the gut microbiota vs. direct physical impact on the host gut, our results are consistent with previous research that found a significant decrease in the consumption of sugar syrup by honey bees ( A. mellifera ) exposed to PS-MPs spheres at the lowest concentrations (10 mg/L vs. 100 mg/L) [ 21 ], (0.5 vs. 5 or 50 mg/L) [ 22 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Female Eastern mosquitofish ( Gambusia holbrooki ) exposed to TB also showed a decrease in the amount of time that they interacted with males compared to non‐exposed fish, whereas exposed and non‐exposed males showed no differences in reproductive behavior (Saaristo et al., 2013 ). Although there is limited research evaluating the potential for sex‐specific effects of MP exposure on aquatic species, male Drosophila melanogaster were reported to have a higher mortality than female flies after exposure (Kholy & Naggar, 2023 ). In the common European hermit crab, Pagurus bernhardus , exposure to MPs decreased the time taken by females to select and enter shells compared to males; however, they were also more likely to choose high‐quality shells (McDaid et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%